Design and Development of a Disposable Superfine Catheter for Visual Examination of Bile Ducts and Related Animal Experiments - Hao, Jin-Yong; Zhang, Yao-Ping; Huang, Xiao-Jun (Frontiers in Surgery, 2022)
Objective: To design and develop a disposable superfine catheter system for visual examination of bile and pancreatic ducts and predict its clinical application value. Methods: The superfine triple-lumen catheter and miniature photography technology were used to design and produce a disposable superfine catheter for visual examination of bile and pancreatic ducts, and animal experiments were conducted to compare said catheter and SpyGlassTM. Results: The designed and developed disposable superfine catheter for visual examination of bile ducts with a diameter of 2.4 mm could enter the third-order and fourth-order bile ducts in the animal liver and also the gallbladder via the cystic duct for observation. The said catheter has a water injection rate of 0.8 ml/s, 0.16 megapixels, a resolution of 400 × 400, a depth of field of 0.3 to 20 mm, and a tilting up angle > 90°. Conclusion: The new disposable catheter for visual examination of bile ducts has a superfine diameter, easier operation, and clearer imaging, and is expected to have a higher clinical practical value.